Ending poverty in South Asia idea that work - Narayan, Deepa (ed.); Glinskaya, Elena (ed.) (Washington D.C, 2007)
This groundbreaking book from South Asia shows how homegrown experiments can be expanded upon to transform the lives of millions of poor women and men in the developing world. It offers valuable lessons in how to make markets and services work to benefit poor people directly, enhancing their dignity and freedom of choice. ""Ending Poverty in South Asia: Ideas That Work"" is an essential tool for policy makers, social scientists, and development practitioners - indeed for all who are interested in tackling poverty and growth issues from the bottom up.
Keywords: Poverty